(untitled) (Journal of Partial Differential Equations, 2020)
In this paper we have obtained the existence of globally smooth solutions to an inhomogeneous nonstrictly hyperbolic system u_t - (v(1 - u))_x = 0, v_t + (12v&sup2 - c_0u)_x = f(u,v) by employing the characteristic method and the fixedpoint theorem in Banach spaces.